Multifold bunch splitting in a high-intensity medium-energy proton synchrotron - Linhao Zhang; Min Chen; Jingyu Tang (Results in Physics, 2022)
Bunch splitting is an RF manipulation method of changing the bunch structure, bunch numbers and bunch intensity in a high-intensity synchrotron that serve as the injector for a particle collider. An efficient way to realize bunch splitting is to use the combination of different harmonic RF systems, such as the two-fold bunch splitting of a bunch with a combination of fundamental harmonic and higher harmonic RF systems. The two-fold bunch splitting and three-fold bunch splitting methods have been experimentally verified and successfully applied in the CERN PS. In this paper, a generalized multifold bunch splitting method is given. The five-fold bunch splitting method using specially designed multi-harmonic RF systems was studied and tentatively applied to the medium-stage synchrotron (MSS), the third accelerator of the injector chain of the Super Proton-Proton Collider (SPPC), to mitigate the pileup effects and collective instabilities of a single bunch in the SPPC. The results show that the five-fold bunch splitting is feasible and both the bunch population distribution and longitudinal emittance growth after the splitting are acceptable, e.g., a few percent in the population deviation and less than 10% in the total emittance growth. Intensity-related effects and beam feedback issues during the splitting process have also been addressed.